High-quality CAD model as a prerequisite for digitalisation of CNC machining process - Ivana Linkeová; Jakub Müller; Michal Stejskal (Graphical Models)
Digitalisation and automation are currently being introduced to CNC machining to increase efficiency and reduce production costs. This trend can result in reduced quality of the final product, especially in CNC machining of molds with complex shapes, where additional manual interventions such as grinding are often necessary. The research in this paper focuses on optimisation in the pre-production phase of the CAD model design. It is shown that the geometric properties of the CAD model, especially the quality of its continuity, significantly influence the resulting accuracy and quality of the machined surface. Increasing the CAD model continuity up to 3rd order automatically smooths the toolpath and improves the accuracy of the machined surface, and therefore the need for subsequent optimisations in the technological phase is also reduced.To investigate the effect of CAD model continuity on CNC machining accuracy, a new Continuity standard representing the continuity of freeform surfaces from 0th to 3rd order was designed and machined by 3-axis milling without any finishing operation. Based on measurements of the manufactured standard, in this paper it is proven that the increasing continuity of the CAD model increases the accuracy of the machining and, at the same time, eliminates the need for additional manual adjustments.